Serum Total Bilirubin and Risk of Cancer: A Swedish Cohort Study and Meta-Analysis - Maria J. Monroy-Iglesias (MDPI AG, 2021)
Bilirubin has strong antioxidant properties that have been hypothesized to be preventive against the development of cancer. Thus, we aimed to investigate the association between serum total bilirubin (STB) and risk of overall and site-specific cancers in the large Swedish Apolipoprotein Mortality Risk (AMORIS) cohort. We also performed a systematic review and meta-analysis for specific cancer types (colorectal, breast and lung). We found no association between high levels of STB and risk of overall cancer. Regarding site-specific cancer, there was an inverse association between increased STB and lung cancer (Hazard Ratio (HR) for the 4th quartile (Q4) vs. Q1: 0.50; 95%CI: 0.44–0.59) and gynecological cancer (HR for Q4 vs. Q1: 0.86; 95%CI: 0.76–0.99). A positive association was found with melanoma (HR for Q4 vs. Q1: 1.25; 95%CI: 1.06–1.47) and breast cancer (HR for Q4 vs. Q1: 1.13; 95%CI: 1.01–1.25) risk. The meta-analysis showed an inverse association between high levels of STB and risk of lung cancer (Relative risk (RR): 0.69; 95%CI: 0.55–0.86). No associations were seen for colorectal and breast cancer risk. Further studies are required to establish if bilirubin can be used as a biomarker for risk assessment and/or as a novel therapeutic target.